2010
DOI: 10.1111/j.1750-3841.2010.01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Soy Sauce and Its Umami Taste: A Link from the Past to Current Situation

Abstract: Soy sauce taste has become a focus of umami taste research. Umami taste is a 5th basic taste, which is associated to a palatable and pleasurable taste of food. Soy sauce has been used as an umami seasoning since the ancient time in Asia. The complex fermentation process occurred to soy beans, as the raw material in the soy sauce production, gives a distinct delicious taste. The recent investigation on Japanese and Indonesian soy sauces revealed that this taste is primarily due to umami components which have mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 66 publications
4
87
0
5
Order By: Relevance
“…Soy sauces can be roughly divided into Chinese type and Japanese type categories. [1] Chinese soy sauce has been popular for centuries due to its unique and pleasant flavour. [2] Soy sauce not only contributes to flavour but also enhances the taste of other ingredients to which it is added, especially the umami taste.…”
Section: Introductionmentioning
confidence: 99%
“…Soy sauces can be roughly divided into Chinese type and Japanese type categories. [1] Chinese soy sauce has been popular for centuries due to its unique and pleasant flavour. [2] Soy sauce not only contributes to flavour but also enhances the taste of other ingredients to which it is added, especially the umami taste.…”
Section: Introductionmentioning
confidence: 99%
“…Soy sauce is a traditional fermented condiment commonly consumed in China, Korea and Japan which is gaining world-wide popularity nowadays due to its various nutritional properties (Lioe et al, 2010). Studies have shown that soy sauce has a promotive effect on human health, such as on iron absorption in human subjects (Baynes et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Soy sauce is a mixture of protein hydrolysate and carbohydrate materials made by the action of enzymes and microorganisms. The product contains amino acids, peptides, reducing sugars and flavor compounds which are formed during the process and which impart tasty flavor with multiple therapeutic and pharmacological actions (Lioe et al, 2010). Fermentation of soy sauce uses enzyme to hydrolyze proteins and starch, that results in the formation of certain amount of substances such as amino acids, and sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Soy sauce was prepared as previously described. 2,7,22) Briefly, equal quantities of steamed soybean meal and roasted wheat were mixed and then inoculated with a pure culture of the A. sojae control strain and/or the glutaminase gene disruptants. The mixtures were cultured for 3 d under controlled a temperature of [25][26][27][28][29][30] C at 95% humidity, resulting in the formation of a dry mash (the soy sauce koji).…”
Section: Methodsmentioning
confidence: 99%
“…Soy sauce contains more than 300 aromatic compounds and generates the five basic tastes: salty, sweet, bitter, sour, and umami. 2,4) The flavors of soy sauce result from the activity of three different microbes-the koji molds, the halophilic lactic acid bacteria, and the salt-tolerant yeasts-used during the koji-making and the moromi fermentation and aging processes. There has been a recent increase in soy sauce popularity worldwide due to its excellent flavor and palatable taste.…”
mentioning
confidence: 99%